PREDIKSI PENYAKIT CARDIOVASKULER DAN PEMBULUH DARAH BERDASARKAN CARTA PREDIKTION DI KECAMATAN BANGGAE - Nanda Putri; Budianto Budianto; Hermin Manganan; Muhrawi Yunding; Saripa Munawarah; Imran Yaman; Aswardi Aswardi; Sakiah Syamsuddin; M.Syikir M.Syikir (Bina Generasi : Jurnal Kesehatan, 2023)
Atherosclerotic cardiovascular disease is a disease caused by plaque buildup on the artery walls, causing functional, anatomical and hemodynamic disorders of the heart and blood vessels. This research was carried out at the Lembang Health Center and the Banggae II Health Center, Majene Regency.Objective : This study was to determine the prevalence of cardiovascular disease in the next 10 years at Lembang Health Center and Banggae II Health Center. Methods: This research is a descriptive study with Non Probability Sampling with Accidental Sampling method. The samples obtained in this study were as many as 80 respondents. Data were analyzed using a computer. Results: The study found that the risk of cardiovascular disease in the next 10 years based on the chart was at most <10% as many as 23 people or 57.5% for Lembang Health Center and 25 people or 62.2% for Bangge II Health Center. And at least 40% as many as 2 people or 5% for Puskesmas Lembang and 3 people or 7.5% for Puskesmas Banggae II. Conclusion: It is hoped that the relevant agencies need to continue to provide health education to the patient's family to maintain and increase the level of knowledge about the importance of avoiding the risk of cardiovascular disease.